Rectal microbiota diversity in Kenyan MSM is inversely associated with frequency of receptive anal sex, independent of HIV status. (1st June 2021) - Gebrebrhan, Henok; Kambaran, Cheli; Sivro, Aida; Adhiambo, Wendy; Siele, Naomi; Becker, Michael G.; Li, Jie; Choi, Sandra; Mwatelah, Ruth S.; Reyes, N. Vincent; Akolo, Maureen; Njogu, Peter; et al.
Abstract : Objective: Both HIV infection and identifying as MSM have been linked to altered rectal microbiota composition, but few studies have studied sexual behavioural associations with rectal microbiota within MSM. In addition, most rectal microbiota studies in MSM have been limited geographically to Europe and North America, and replication of findings in lower and middle-income countries is lacking. Design: A cross-sectional study. Methods: We enrolled MSM from Nairobi, Kenya, and determined their HIV/sexually transmitted infection status. Rectal specimens were obtained for 16s rRNA sequencing of the rectal microbiota, and sexual behaviour was characterized using a standardized questionnaire. Microbiome differences were modelled using nonparametric statistics, Bray-Curtis ecological distance metrics and analyses of differential taxa abundance. Multivariable linear regression was used to model HIV status and recent sexual activity as predictors of alpha diversity, controlling for a range of covariates. Results: Alpha diversity was consistently lower in Kenyan HIV-infected MSM ( n  = 80), including those on antiretroviral therapy (ART) compared with HIV-uninfected MSM. A statistical trend was observed for clustering of HIV status by Prevotella or Bacteroides dominance ( P  = 0.13). Several taxa were enriched in HIV-positive men, including Roseburia, Lachnospira, Streptococcus and Granulicatella. Receptive anal sex with several types of sexual partners (paying, regular, casual) was associated with lower Chao1 and Simpson diversity, independent of HIV status, while HIV infection was associated lower Chao1 ( P  = 0.030) but not Simpson diversity ( P  = 0.49). Conclusion: Both HIV infection and sexual behaviour were associated with rectal microflora alpha diversity, in particular richness, but not Prevotella spp. dominance, in Kenyan MSM. Associations were more robust for sexual behaviour. Abstract : Supplemental Digital Content is available in the text